Aetiologies of creeping eruption: 78 cases. (May 2014) - Vanhaecke, C.; Perignon, A.; Monsel, G.; Regnier, S.; Paris, L.; Caumes, E.
<x xml:space="preserve">Abstract</x> What's already known about this topic? As hookworm‐related cutaneous larva migrans (HrCLM) is the most common cause of creeping eruption, the disease HrCLM and the sign of creeping eruption have been confused for a long time. What does this study add? This is the first study to report the different aetiologies of creeping eruption and show that, besides HrCLM, several diseases can give rise to this clinical sign.